Habitar la colonialidad. Una autoetnografía sobre la colonización interior. - Anastasio, María J. (Re-visiones, 2024)
This essay proposes an autoethnographic exercise focused on my village, Nuevo Amatos, Salamanca, one of the three hundred villages created by the Francoist government through policies of the National Institute of Colonization. The essay centers on the experience of my family and my village, engaging in conversation with critical studies about the nature and functioning of the INC. I propose a reflection based on my concrete experience as the daughter of a family of "settlers" and the literal heir of the properties acquired as a result of the colonization project. I suggest that, if as multiple authors have argued, this colonization project involved the construction of an ideal rural subject, to what extent both my community, my family and I are the result of that construction.